A 3D printed patient-specific dual compartment breast phantom for validating MRI acquisition and analysis techniques (Transactions on Additive Manufacturing Meets Medicine, 2019)
Anthropomorphic phantoms are essential tools that are used to validate MRI acquisition and analysis techniques. 3D printing technologies are rapidly advancing and can be utilized to achieve anatomically realistic geometries that are not attainable using traditional manufacturing methods. Herein, we present the design of a 3D printed anthropomorphic breast phantom that includes the key breast tissue compartments which are filled with desired tissue-mimicking fluids. The breast phantom can be used for validating MR, coil development, safety evaluation and pulse sequence evaluation.